2006
DOI: 10.1186/1746-160x-2-14
|View full text |Cite
|
Sign up to set email alerts
|

Experience versus complication rate in third molar surgery

Abstract: ObjectivesThe records of 1087 patients who underwent surgical removal of third molar teeth were prospectively examined to analyse the possible relationship between postoperative complications and the surgeon's experience parameter.Method and materialsSeven surgeons (three specialists in surgical dentistry [specialists SD] and four oral and maxillofacial Senior House Officers [OMFS residents]) carried out the surgical procedures. For each patient, several variables were recorded including age, gender, radiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
62
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 23 publications
(34 reference statements)
3
62
1
5
Order By: Relevance
“…The findings of this study are very similar to those of the preliminary study by Jerjes et al, 1 with a greater number of parameters of postoperative complications being statistically more signifi cant. Previous studies have suggested that a surgeon's experience may be a factor in the frequency of complications.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The findings of this study are very similar to those of the preliminary study by Jerjes et al, 1 with a greater number of parameters of postoperative complications being statistically more signifi cant. Previous studies have suggested that a surgeon's experience may be a factor in the frequency of complications.…”
Section: Discussionsupporting
confidence: 82%
“…29 The use of a preoperative chlorhexidine rinse and resorbable gelatine or cellulose sponges have been suggested to reduce the incidence of alevolar osteitis, infection and bleeding. 1,11,16,24 Numbness of the lip and tongue are symptoms that a patient may rate as having a high signifi cance compared with some of the other complications described. The rates of nerve damage are variable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the evaluation of trismus, Waseem et al (22) reported that the amount of mouth opening following impacted third molar surgery with less than 25mm shows trismus criteria. Bamgbose et al (23) measured the trismus values at 1st, 2nd and 7th days after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore in this study, the young patients (18)(19)(20)(21)(22)(23)(24)(25) were included. For this reason, we considered that there were no serious complications observed after impacted third molar surgery.…”
Section: Discussionmentioning
confidence: 99%